2016
DOI: 10.1109/jsac.2016.2577319
|View full text |Cite
|
Sign up to set email alerts
|

Scalable Cache Management for ISP-Operated Content Delivery Services

Abstract: Abstract-Content Delivery Networks (CDNs) have been the prevalent method for the efficient delivery of content across the Internet. Management operations performed by CDNs are usually applied based only on limited information about Internet Service Provider (ISP) networks, which can have a negative impact on the utilization of ISP resources. To overcome these issues, previous research efforts have been investigating ISPoperated content delivery services, by which an ISP can deploy its own in-network caching in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…This fact, together with the pressure that content publishers face with the increasing costs of timely video delivery and mobility support [20], [21] is foreseen to bring ICN closer to deployment [22]. Research on ICN in-network caching has also found applicability in other areas such as Telco CDNs [23] and some aspects of it may find deployment in 5G and the Internet of Things (IoT).…”
Section: Current Practices: Network Difficult To Tame -Bring Content mentioning
confidence: 99%
“…This fact, together with the pressure that content publishers face with the increasing costs of timely video delivery and mobility support [20], [21] is foreseen to bring ICN closer to deployment [22]. Research on ICN in-network caching has also found applicability in other areas such as Telco CDNs [23] and some aspects of it may find deployment in 5G and the Internet of Things (IoT).…”
Section: Current Practices: Network Difficult To Tame -Bring Content mentioning
confidence: 99%
“…In our model, we assume that the request popularity exponent has the same value z at each user, but the ranking/order of the items within the Zipf distribution is different. It is well known that the user demand is characterized by a) the total volume of requests for each item in the network, which defines the global content popularity (GCP), and b) the number of locations where each content is requested, defining the geographic distribution of the interests (GDI) [52] and [53]. Here, despite the fact that we assume a very specific and small area where users are deployed we assume the same model (different ranking/order of the items within the Zipf distribution at each user) to examine the performance of the proposed approach in a more generic scenario, since homogeneous popularity of items among the users would definitely benefit the overall system performance.…”
Section: Evaluation Setup and Metricsmentioning
confidence: 99%
“…Note that 10 6 items is not meant to represent the current Internet content space. Instead, this set consists of the items that an ISP-operated Content Delivery Service [27] can store in its network. We also assume that each content item has the same size to simplify the cache size provisioning in the experiments.…”
Section: Evaluation Setup and Metricsmentioning
confidence: 99%